Price Manipulation During the Indonesian Presidential Election of 2019: Does it Matter Toward Return, Volatility and Liquidity? - Kris Ossy Novian; Intan Nurul Awwaliyah; Hadi Paramu (Conference Series, 2020)
The main purpose of this research is to evaluate if stocks indicated political content during the 2019 Indonesia’s presidential election in the form of price manipulation. This study uses a quantitative method by employing an independent sample t-test to test the hypothesis. Sample formation is divided into two broad categories which are affiliated company stocks and non-affiliated company stocks. Data gathered in this study are return, volatility, and liquidity from March 23 to April 17, 2019. The results show that there is no evidence of price manipulation during the presidential election in those three variables including return (0.0870), volatility (0.5630) and liquidity (0.0800). The overall null hypothesis cannot be rejected since the t-statistics is smaller than the t-table (2.0243). However, there is an indicative of the stock price decrease which occurred during a period of observation from the 2019 presidential election. Although the price manipulation is not evidence during the election, yet strengthening the stock market regulation is necessary in order to improve investor’s confidence to invest in Indonesia in particular during political events.